La mistificazione delle Americhe. La cosiddetta “Profezia Maya” del 2012 (Altre Modernità, 2013)
The fluidity of post-modern vision and interaction with the tourist market and mass media are leading to increasing mythification and commodification of Native American cultures.In this article, we provide some case histories revolving around the so-called 2012 Maya Prophecy, for example Eugenia Casarin Limón, who in Mexico presents herself as a psychotherapist and member of an originally French neo-Hermetic organization, whereas in Italy she appears as a "Maya priestess"; or the better known José Argüelles, whose cultural background is entirely North American and European.Argüelles has made use of an ethnic Maya, Hunbatz Men, who however drew inspiration, not from traditional sources, but from a self-styled Gnostic movement, founded by the German adventurer Arnold Krumm-Heller; and the Mexican author Martínez Paredez, who inspired the symbolic work of Argüelles, was in turn inspired by a French Freemason, Augustus Le Plongeon.Application by Argüelles and others of the I Ching to the so-called Maya Prophecy is especially interesting because of the changing meaning of this Chinese work to the West, from the times of the Jesuit missions to today's cyberculture.The Maya Prophecy has much more to tell us about “Western” culture than about the Mesoamerican world.